Financial of Management: Concept, Success Indicators, and Evaluation (Literature Review) - Teguh Maianto; Sova, Maya; Zulaekah, Zulaekah; Mulyani Setyowati, Tri; Arif Hernawan, Moch (Greenation International Journal of Economics and Accounting, 2024)
Articles related to financial management: concepts, success indicators and evaluation are scientific articles of literature review in the scope of financial management science. This article aims to make a hypothesis about the relationship between factors, which can then be used for further research in the field of financial management. The approach used in this study is descriptive qualitative. The data used in this study comes from previous studies that are still relevant to this study. The data used in this study were obtained from academic media, reputable journals, and academic platforms such as Scopus, Emeral, WoS, DOAJ, EBSCO, SINTA, GARUDA journals and digital books. The results of this study are as follows: 1) Concepts play a role in financial management; 2) Success indicators play a role in financial management; and 3) Evaluation plays a role in financial management.